Synthesis and characterisation of dyeintercalated nickelaluminium layereddouble hydroxide as a cosmetic pigment - Kovalenko, Vadym; Kotok, Valerii; Yeroshkina, Anastasiya; Zaychuk, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
Dyeintercalated layered double hydroxides (LDH) are modern promising pigments for paint and cosmetics industry. For the preparation of highquality cosmetic pigments, particularly for nail polish, it was proposed to use not only intercalation but also chemisorption. For the pigment synthesis, NiAL LDH was chosen, along with murexide (Ammonium (purpurate) 2,6dioxo5[(2,4,6trioxo5hexahydropyrimidinylidene)amino]3Hpyrimidin4olate), in which colored purpurate anion is able to form complex compounds with Ni2+. The murexideintercalated (murexide amount for intercalation only) and murexideintercalatedchemisorbed (murexide amount for Ni2+) NiAl LDH pigments were synthesized and used for the preparation of nail polish samples. The crystallographic composition was studied by means of XRD analysis. The color parameters (coordinates of color and chromaticity, dominant wavelength and color purity) of pigment powders and nail polish samples with these pigments<s> </s>have been studied using a color comparator. Organoleptic characteristics of pigment and nail polish samples were studied. The positive influence of chemisorption was shown: murexideintercalatedchemisorbed pigment is easily ground, with the formation of highly dispersed powder, which during the preparation of nail polish was easily dispersed with the formation of stable yellow samples (dominant wavelength 583 nm) with high color purity of 43 %. Also, high covering ability of the murexideintercalatedchemisorbed pigment was shown: highquality, opaque, colored nail polish coat was formed at the pigment content of 45 %, 30 % and 15 % (wt.). For the synthesis of such pigments, it was recommended to choose anionic dyes that can form coordination bonds with LDH cations.